Manajemen Keuangan, Valuasi Perusahaan, dan Value Creation: Peran Learning Orientation dan Marketing Performance Pada Perguruan Tinggi Swasta di Jawa Barat - Hasti Pramesti Kusnara; Herry Achmad Buchory; Rizky Ferari Oktavian; Siti Wulansari; Ignatius Oki Dewa Brata (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to systematically examine the relationships among financial management, company valuation, and value creation, as well as the role of learning orientation and marketing performance in Private Universities (PTS) in West Java through a Systematic Literature Review (SLR) approach using the PRISMA 2020 protocol. Out of 347 articles identified from Scopus, Google Scholar, DOAJ, and Garuda databases, 32 articles met the inclusion criteria and were analyzed in depth. The synthesis reveals that effective financial management positively contributes to company valuation through enhanced profitability and operational efficiency. Value creation, measured through Economic Value Added (EVA) and Market Value Added (MVA), is consistently influenced by the organization's learning orientation capacity in responding to competitive environmental changes. Marketing performance serves as a partial mediator between learning orientation and company valuation in the context of PTS in West Java. These findings enrich the strategic management literature and provide